Relevansi Rancang Bangun Metode Alamiah dalam Pembelajaran Bahasa Kedua untuk Anak Usia Dini - Mohd. Hafrison (Fakultas Bahasa dan Seni UNP, 2010)
Learners are the subject rather than object in the learning process. Therefore, the implementation of learning should be able to give responsibility to the learners in managing the acquisition and learning results. Similarly, in learning the Indonesian language, learning the language is not directed so that learners understand the rules of grammatical and literary, but are able to develop the potential that exists in itself related to the communicative potential of language. This goal can be achieved if the learning is done by using the right approach, especially for young children. One method suggested is a natural method. The use of this method is based on the theoretical basis of language that emphasizes the role of transformational linguistic semantics as a builder and an adhesive element of meaning, both at the level of morphology and syntax. Learning theory is the foundation of cognitive psychology that emphasizes the role of cognitive ability as the basis for the development of knowledge, skills and attitudes. The application of this method is very relevant to the language development of elementary-school-age children because the achievement of learning objectives is done naturally. To make the learning takes place naturally, in the process of learning, teachers are expected to be able to present comprehensible input as much as possible. The assistance provided is aimed to develop the ability to understand. Tool-visual aids, for example, can be used to perform the exposure of vocabulary. The focus of learning is listening and reading activities, while the ability to speak and write will evolve slowly and sustainably in line with the ability to understand it. To lower the affective filter, learners are directed to engage in meaningful communication, rather than on language forms. Correspondingly, the input that was developed by teacher should be an interesting and challenging input.. Key words: Natural Method, Second Language Learning, Early Education